اثر يوم الأسبوع والعوامل الأخرى في أسعار و حركة الاسهم - د. طلال الججاوي; د. عبدالناصر إبراهيم نور (PROSPECTIVE RESEARCHES, 2023)
On the international level, there is an effective day-of-the-week which affects markets except, Taiwan and Amman. This research tries to test this phenomenon in BSE and introducing two variables to determine the effect of that day through three hypotheses. It has been found that there is no dayof-the-week effecting BSE and there is no relationship between personality skills (Variable 1) and the day-of-the-week. Also there is a relationship between political, economical, financial and general conditions (variable 2) and the day-of-the-week.